Analisis Pengaruh Prisma Akresi dan Patahan Splay terhadap Deformasi Permukaan akibat Gempa Mentawai 2010 melalui Pemodelan Numerik 3D - Alvina Kusumadewi Kuncoro; Wahyu Srigutomo; Umar Fauzi (Jurnal Fisika Unand, 2025)
The Southern Mentawai Segment is located in the Sumatra Subduction Zone, which is part of the accretionary wedge. The accretionary wedge is the most complex tectonic structure in the world within its material and geometrical structure. The 2010 South Mentawai earthquake, with magnitude Mw~7.8, was accompanied by a tsunami that was larger than expected for its magnitude, classifying it as a tsunami earthquake. This study analyze the effect of the accretionary wedge and faults in the South Mentawai Segment on surface deformation using 3D finite element modeling. The geometric model was constructed in four configurations: a model without an accretionary wedge, a model without an accretionary wedge but with splay fault, a model with an accretionary wedge, and a model with both accretionary wedge and splay fault. The results indicate that the model with the accretionary wedge aligns better to the data observed at GPS stations, particularly for the vertical deformation. The presence of splay faults in the model increases the vertical deformation by up to twice, both for the model with and without the accretionary wedge. A better understanding of the subsurface structure enables more precise identification of areas with potential earthquake-triggered tsunamis and more accurate surface deformation estimation.